Effect of temperature on incubation period, embryonic mortality, hatch rate, egg water loss and partridge chick weight (Rhynchotus rufescens) - Nakage, E. S. [UNESP] (2003)
The aim of this study was to determine the effects of incubation temperature (34.5; 35.5; 36.5; 37.5 and 38.5ºC), on incubation period, embryonic mortality, hatching rate, water loss and chick weight at hatch, using daily incubation of partridge (Rhynchotus rufescens) eggs. The highest hatching percentage was obtained between 35.5 and 36.5ºC. Incubation length and temperature were inversely proportional. Water loss was lower in eggs incubated at low temperatures as compared to high temperatures. There was no difference among incubation temperatures in absolute and relative hatchling weights. Early embryonic mortality increased at low temperatures (<35.5ºC), whereas intermediate and late embryonic mortality increased at high temperatures (>36.5ºC). Our results show that, under conditions of daily incubation of eggs in the same incubator, higher hatching rate can be obtained using temperatures between 35.5ºC and 36.5ºC; incubation temperature is inversely proportional to incubation length, and absolute and relative weights of partridge chicks are not affected by incubation temperature.